Using the Improvement of the Fixed Point Iterative Method in Solving Fredholm Integral Equations - Abbas Al-Bayati (Al-Rafidain Journal of Computer Sciences and Mathematics)
In this paper an iterative method for the fixed point is used to obtain an approximation solution for the Fredholm integral equations of the second kind by using several problems with different accuracy .Also we have proposed a successful improvement for the iterative fixed point method. A number of different tests are solved and compared in order to study the effectiveness of the proposed technique.